(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores youth slang as a dynamic linguistic phenomenon and a reflection of contemporary social processes. It examines the functional and structural characteristics of slang, the influence of globalization and digital media, and the sociocultural meanings embedded in slang expressions. Based on concrete examples from Russian-speaking youth, the study reveals how slang serves as a tool for identity formation, social critique, and emotional expression.